Periprosthetic joint infection of megaprostheses for oncologic and non-oncologic indications—IMPLANT retention or removal? A retrospective cohort study of 50 cases - Benjamin Schlossmacher; Elena Strasser; Vincent Lallinger; Florian Pohlig; Ruediger von Eisenhart-Rothe; Igor Lazic (Arthroplasty)
Abstract Background and purpose Periprosthetic joint infection (PJI) is a devastating but rare complication. Its incidence ranges between 1%–2% in primary arthroplasties. However, infection rates are much higher in megaprostheses (15%–43%). Revision of megaprostheses (MP) is a highly complex procedure associated with massive bone loss, so that implant retention occurs as a viable initial therapy option even in chronic infections. Unfortunately, literature regarding therapy strategies and outcome reports for PJI in MP is scarce. Reinfection rates are reported to be between 22 and 58%. We therefore proposed the following questions: What is the overall outcome of PJI in MP in our cohort, and are there significant differences in infection-free survival between various surgical strategies? Methods In this retrospective cohort study, 50 cases of PJI in MP treated from 2010 to 2022 were identified. The median (IQR) age was 70.5 (16.3) years. Mean follow-up was 19.0 months. Treatment outcome was categorized following international consensus criteria. Results Overall infection-free implant survival was 42.0%. 7 patients died in direct association with the ongoing PJI, and 7 had to undergo amputation. Two-stage revision had the highest success rate of 71.4% (5/7), followed by multi-stage surgery (57.1%; 4/7), DAIR (38.7%; 12/31), and single-stage revision (0%; 0/5) (P = 0.009). Overall, treatment success rates following DAIR were 55.6% (10/18) for acute and 15.4% (2/13) for chronic infections (P = 0.027). The most common pathogens were coagulase-negative Staphylococci (42.0%; 21/50) and Staphylococcus aureus (34.0%; 17/50). Gram-negative pathogens accounted for 16.0% (8/50). Conclusions PJI in MP remains a devastating complication with low success rates. Two-stage revision is the most promising treatment option, but it requires patients to be able to cope with the burden of multiple surgeries. DAIR cannot be recommended as a definitive treatment for chronic cases (15% success rate) and should be questioned in acute cases (56% success rate), as infection eradication is rare. DAIR can be considered a low-impact surgery for infection control if more extensive surgery is not viable. Video Abstract